Self-Enforcing Trade Agreements : Evidence from Time-Varying Trade Policy - Bown, Chad P.; Crowley, Meredith A. (2012)
This paper estimates a model of a government making trade policy adjustments under a self-enforcing trade agreement in the presence of economic shocks. The empirical model is motivated by the formal theories of cooperative trade agreements. The authors find evidence that United States' use of its antidumping policy during 1997-2006 is consistent with increases in time-varying "cooperative" tariffs, where the likelihood of antidumping is increasing in the size of unexpected import surges, decreasing in the volatility of imports, and decreasing in the elasticities of import demand and export supply. The analysis finds additional support for the theory that some US antidumping use is consistent with cooperative behavior through a second empirical examination of how trading partners responded to these new US tariffs. Even after controlling for factors such as the expected cost and benefit to filing a WTO dispute or engaging in antidumping retaliation, the analysis find that trading partners are less likely to challenge such "cooperative" US antidumping tariffs that were imposed under terms-of-trade pressure suggested by the theory.